Use of LSPIV in assessing urban flash flood vulnerability - Guillén, Nicolás Federico (2017)
The probability of the occurrence of urban flash floods has increased appreciably in recent years. Scientists have published various articles related to the estimation of the vulnerability of people and vehicles in urban areas resulting from flash floods. However, most published works are based on research performed using numerical models and laboratory experiments. This paper presents a novel approach that combines the implementation of image velocimetry technique (large-scale particle image velocimetry—LSPIV) using a flash flood video recorded by the public locally and the estimation of the vulnerability of people and vehicles to high water velocities in urban areas. A numerical one‐dimensional hydrodynamic model has also been used in this approach for water velocity characterization. The results presented in this paper correspond to a flash flood resulting on November 29, 2012, in the city of Asunción in Paraguay. During this flash flood, people and vehicles were observed being carried away because of high water velocities. Various sequences of the recorded flash flood video were characterized using LSPIV. The results obtained in this work validate the existing vulnerability criterion based on the effect of the flash flood and resulting high water velocities on people and vehicles.